Classification and Microvascular Flap Selection for Anterior Cranial Fossa Reconstruction - Vargo, James D.; Przylecki, Wojciech; Camarata, Paul J.; Andrews, Brian T. (Journal of Reconstructive Microsurgery, 2018)
Background Microvascular reconstruction of the anterior cranial fossa (ACF) creates difficult challenges. Reconstructive goals and flap selection vary based on the defect location within the ACF. This study evaluates the feasibility and reliability of free tissue transfer for salvage reconstruction of low, middle, and high ACF defects.Methods A retrospective review was performed. Reconstructions were anatomically classified as low (anterior skull base), middle (frontal bar/sinus), and high (frontal bone/soft tissue). Subjects were evaluated based on pathologic indication and goal, type of flap used, and complications observed.Results Eleven flaps in 10 subjects were identified and anatomic sites included: low (n = 5), middle (n = 3), and high (n = 3). Eight of 11 reconstructions utilized osteocutaneous flaps including the osteocutaneous radial forearm free flap (OCRFFF) (n = 7) and fibula (n = 1). Other reconstructions included a split calvarial graft wrapped within a temporoparietal fascia free flap (n = 1), latissimus myocutaneous flap (n = 1), and rectus abdominis myofascial flap (n = 1). All 11 flaps were successful without microvascular compromise. No complications were observed in the high and middle ACF defect groups. Two of five flaps in the low defect group using OCRFFF flaps failed to achieve surgical goals despite demonstrating healthy flaps upon re-exploration. Complications included persistent cerebrospinal fluid leak (n = 1) and pneumocephalus (n = 1), requiring flap repositioning in one subject and a second microvascular flap in the second subject to achieve surgical goals.Conclusion In our experience, osteocutaneous flaps (especially the OCRFFF) are preferred for complete autologous reconstruction of high and middle ACF defects. Low skull base defects are more difficult to reconstruct, and consideration of free muscle flaps (no bone) should be weighed as an option in this anatomic area.
Keywords: anterior cranial fossa; cranioplasty; microvascular surgery; free tissue transfer